2011
DOI: 10.1152/ajpheart.00148.2011
|View full text |Cite
|
Sign up to set email alerts
|

Persistent sympathoexcitation long after submaximal exercise in subjects with and without coronary artery disease

Abstract: There is an increased risk of cardiac events after exercise, which may, in part, be mediated by the sympathoexcitation that accompanies exercise. The duration and extent of this sympathoexcitation following moderate exercise is unknown, particularly in those with coronary artery disease (CAD). Twenty control subjects (mean age, 51 years) and 89 subjects with CAD (mean age, 58 years) underwent two 16-min bicycle exercise sessions followed by 30-45 min of recovery. Session 1 was performed under physiological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 43 publications
3
37
0
Order By: Relevance
“…The heart rate response to exercise and recovery is shown in Table 2. As previously reported [25], all groups had persistent elevation of the heart rate at 30 and 45 minutes of recovery as compared to the resting heart rate (p<0.01 and p<0.03, respectively).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The heart rate response to exercise and recovery is shown in Table 2. As previously reported [25], all groups had persistent elevation of the heart rate at 30 and 45 minutes of recovery as compared to the resting heart rate (p<0.01 and p<0.03, respectively).…”
Section: Resultssupporting
confidence: 85%
“…While evaluation of heart rate changes and plasma catecholamine changes in the post-exercise recovery period did not identify differences among the study groups [25], there were differences in the recovery HRV findings among the group. The prognostic significance of HRV after exercise has not been studied, but represents an intriguing possibility based on the present findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data concur with the view that the intensity of PNS reactivation steadily increases further until 4 minutes into recovery and remains relatively constant thereafter. 8 In patients with and without CHD, Wang et al 68 found that PNS effects on HR reached a peak about 2 minutes into recovery from exercise, whereas SNS effects dissipated more slowly, with significant increases in plasma catecholamines and HR even 45 minutes after exercise. Johnson and Goldberger 9 suggest that late HRR reflects withdrawal of SNS drive of exercise, with lower HRR indicating more persistent SNS excitation.…”
Section: Discussionmentioning
confidence: 99%